Effects of mental fatigue on the psychophysiological responses, kinematic profiles, and technical performance in different small-sided soccer games - Soylu, Yusuf; Ramazanoglu, Fikret; Arslan, Ersan; Clemente, Filipe (Biology of Sport, 2022)
The purpose of this study was to assess the effects of mental fatigue (MF) on the psychophysiological responses, kinematic profiles, and technical performance of young soccer players in small-sided games (SSGs). Twenty-four young soccer players (age: 15.9 ± 1.0 years) played 2vs2, 3vs3, and 4vs4 SSGs consisting of four bouts (with two-minute passive rest periods between bouts) under two different playing conditions: MF+SSGs and SSGs. The heart rate, total distance covered, and technical performance of each player were monitored during all SSGs, and the rating of perceived exertion, visual analogue scale, and Rating Scale Mental Effort values were determined after each bout. The Physical Activity Enjoyment Scale (PACES) and Brunel Mood Scale (BRUMS) were also determined at the end of each SSG. The results demonstrated that all MF+SSGs induced higher psychophysiological responses (p ≤ 0.05) than SSGs, except regarding the PACES responses. By contrast, the SSGs group covered a greater total distance (p ≤ 0.05) than the MF+SSGs group. During SSGs, the players’ technical performances (in terms of lost balls and unsuccessful passes) were negatively affected after MF (p ≤ 0.05). The results of this study indicate that both PACES scores and mood responses were negatively affected after the MF intervention. Coaches could use the MF intervention before SSGs to improve soccer-specific technical and decision-making performances in young soccer players.